Несовершеннолетний в семейном насилии [Articol] - Гырла, Лилия (CEP USM, 2022)
The peculiarity of the subject of legal regulation of juvenile law is the presence of a minor subject, which is a mandatory participant in all juvenile legal relations, on the one hand, and a subject of legal relations involved in the upbringing, prevention of possible criminal behavior and social security of the child, on the other, which determines the peculiarity of this legel relationship. According to modern data, adolescent victimization is understood as a kind of ability to become a victim of negative phenomena. There are certain qualities in personality of teenager that make him, under certain circumstances, a victim, and more quickly and easily than another who does not have these personality qualities. Undoubtedly, the nature and quality of communication between children and their parents in the family affects the process of schooling, relationships in the classroom, and interaction with teachers. A significant role in the origin of delinquent behavior is played by the microsocial situation, namely: asocial and antisocial environment (alcoholism of parents; asocial and antisocial family / company); neglect; large and incomplete family; intra-family conflicts; chronic conflicts with significant others.
Keywords: несовершеннолетние; minor; juvenile law; juvenile delinquency; family crimes; ювенальное право